2019
DOI: 10.12659/msm.912858
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopamine Suppresses Human Esophageal Carcinoma Cell Growth by Inhibiting Glioma-Associated Oncogene Protein-1, a Marker of Human Esophageal Carcinoma Progression

Abstract: Background Esophageal carcinoma is a common gastrointestinal tumor in humans. Cyclopamine, a Hedgehog (Hh)-pathway-specific inhibitor, is an effective chemotherapeutic drug for suppressing tumor cell differentiation, with unclear mechanisms. We investigated glioma-associated oncogene protein-1 (Gli-1) expression in human esophageal carcinoma tissue and the inhibition of cyclopamine on EC9706 esophageal carcinoma cell growth. Material/Methods Gli-1 in tumor tissue was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The human ESCC cell lines EC109 and EC9706 were gifts from Dr. Jing Yu and Dr. Xianbin (Department of Gastroenterology, The First Affiliated Hospital of Shantou University Medical College, China) (Peng et al, 2020;Yu et al, 2019). Cells were maintained in RPMI-1640 medium (HIMEDIA, Mumbai, India) with 10% fetal bovine serum (FBS; HyClone, Logan, UT, United States) in an atmosphere of 5% CO 2 at 37 °C.…”
Section: Cell Lines and Culturementioning
confidence: 99%
“…The human ESCC cell lines EC109 and EC9706 were gifts from Dr. Jing Yu and Dr. Xianbin (Department of Gastroenterology, The First Affiliated Hospital of Shantou University Medical College, China) (Peng et al, 2020;Yu et al, 2019). Cells were maintained in RPMI-1640 medium (HIMEDIA, Mumbai, India) with 10% fetal bovine serum (FBS; HyClone, Logan, UT, United States) in an atmosphere of 5% CO 2 at 37 °C.…”
Section: Cell Lines and Culturementioning
confidence: 99%
“…A large number of studies showed the SHH pathway to be silent in normal mature esophageal epithelial cells, but in dysplasia and cancer, the SHH pathway is activated ( Zhu et al., 2011 ; Okumura et al., 2014 ; Wadhwa et al., 2017 ). The SHH pathway inhibitor, CPM, has been used in the clinical treatment of cancer ( Berman et al., 2003 ; Yu et al., 2019 ). We previously confirmed that SHH can regulate the proliferation and differentiation capacity of mouse esophageal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant activation of the glioma‐associated oncogene Gli‐1 is a key factor in the hippocampal signaling pathway, and this gene also plays an inhibitory role in the growth of EC 9706 esophageal cancer cells and so on. [ 24 ] Gene expression in glial carcinoma and esophageal carcinoma has some similarity. In order to accurately distinguish glioma and esophageal cancer and improve patients' survival rate, we attempt to develop a rapid, nondestructive, and sensitive method that is based on molecular vibrational spectroscopy to distinguish the two tumor diseases.…”
Section: Introductionmentioning
confidence: 99%